ASGE guidelines for the appropriate use of upper endoscopy: Association with endoscopic findings - Rossi, Angelo; Bersani, Gianluca; Ricci, Giorgio; DeFabritiis, Giovanni; Pollino, Valeria; Suzzi, Alessandra; Gorini, Beatrice; Alvisi, Vittorio (Gastrointestinal endoscopy, 2002)
Background: This prospective study examined the appropriate use of EGD in an open-access system with the American Society for Gastrointestinal Endoscopy (ASGE) guidelines and determined whether the ASGE guidelines were associated with relevant endoscopic findings. Methods: In a cohort of 1777 consecutive patients referred for open-access EGD, the proportion of patients who underwent EGD for appropriate indications was prospectively assessed. The relationship between appropriateness and the presence of clinically relevant endoscopic diagnoses was assessed by calculating (1) the likelihood ratio, positive and negative, of the indications; and (2) the change in the probability of relevant endoscopic diagnoses in the presence of the ASGE criteria. Results: The rate for EGDs “generally not indicated” was 15.6%. Relevant endoscopic diagnoses were present in 47.4% of cases with ASGE indications versus 28.8% of patients without appropriate indications as defined by the ASGE criteria (OR: 2.23; 99% CI [1.55, 3.22]; p < 0.01). A similar difference was observed for erosive gastritis (OR: 1.86; 99% CI [1.17, 2.95]; p < 0.01), erosive esophagitis (OR: 1.48; 99% CI [0.87, 2.52]; p < 0.05), and Barrett's esophagus (OR: 9.76; 99% CI [0.72, 132]; p < 0.05). The pretest probability of finding a relevant endoscopic diagnosis was modified slightly when an ASGE indication(s) was present and decreased markedly when ASGE criteria were absent. Conclusions: The use of the ASGE guideline for appropriate indications for EGD can improve patient selection for the procedure. However, to avoid missed diagnoses of serious disease, use of the guidelines must be tailored to the specific clinical setting. (Gastrointest Endosc 2002;56:714-9.)